Distribution Of Helminth Parasites In Size Groups And Organs Of Hilsa Shad, Tenualosa Ilisha (Dhaka University Journal of Biological Sciences, 2012)
Demographic parameters such as prevalence, intensity, abundance etc. of the component parasites of hilsa (Tenualosa ilisha) collected from 11 sites under 3 different habitats all over Bangladesh were calculated as a function of host size, sex and organ of infection. Organ preference of component parasite species did not show any variation in the hilsa collected from the three ecological habitats. All the trematodes were found exclusively in cardiac stomach and intestine. Nematodes were less organ specific. Abundance of total parasites in cardiac stomach and intestine were not significantly different from each other but that of stomach and mesenteries were significantly different from each other and from cardiac stomach or mesentery. In freshwater hilsa differences between most of the lower length groups were not significant (p > 0.05). In brackish water hilsa parasite burden were significantly different between length groups. In marine hilsa mean parasites burden in different length classes were not significant (p > 0.05). DOI: http://dx.doi.org/10.3329/dujbs.v21i1.9745 DUJBS 2012 21(1): 55-65